Research on the relative humidity changes of the controlled atmosphere environment for redried tobacco storage - Y. Y. Zhu; F. Xiao; Q. P. Fu; L. Dai; Y. B. Qu; H. Zhang; Z. J. Zhang; W. Yin; T. T. Fan; D. F. Yin; J. Yin (Scientific Reports)
Abstract To study the ambient relative humidity changes during the controlled atmosphere alcoholization for redried tobacco storage. Firstly the critical factors of relative humidity of the controlled atmosphere for no tobacco and redried tobacco were researched, respectively. Then the models had been constructed and validated. The results showed that the relative humidity of the controlled atmosphere environment for no tobacco had significant correlation with nitrogen volume concentration and temperature, had insignificant correlation with oxygen volume concentration. And the relative humidity of the controlled atmosphere environment for redried tobacco had significant correlation with the nitrogen volume concentration, temperature, and moisture content of redried tobacco, and the interactions between the other factors were significant except for the interaction between the temperature and the nitrogen volume concentration, which was not significant. The relative errors of the relative humidity of the controlled atmosphere environment for no tobacco and redried tobacco were within 8% and 4%, respectively. Therefore quantitatively analyze and predict the relative humidity changes of the controlled atmosphere environment for redried tobacco storage with models to determine whether it meets the alcoholization quality of redried tobacco based on the equilibrium relative humidity of the redried tobacco storage through regulating the relative humidity of the controlled atmosphere environment. It can control precisely the alcoholization process and accelerate the alcoholization quality promotion of tobacco.